Primary Education Expansion and Quality of Schooling: Evidence from Tanzania - Christine Valente (Institute for the Study of Labor (IZA), 2015)
The rapid increase in primary enrollment seen in many developing countries might worsen schooling quality. I estimate the effect of enrollment growth following the removal of primary school fees in Tanzania and find that it led to large increases in the pupil-teacher ratio and a reduction in observable teacher quality, but rule out a substantial effect on test scores overall. These results are robust to instrumenting enrollment growth using predetermined fertility and migration decisions, and not driven by compositional changes. In urban areas, however, where baseline achievement was higher, test scores deteriorated where enrollment growth was larger.
Keywords: I21; I28; O15; 330; universal primary education; pupil-teacher ratio; test scores; Tanzania